Penggunaan Kembali Basis Pengetahuan dengan Representasi Bingkai dalam Aplikasi Kecerdasan Buatan - Anjar Priandoyo (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Development and maintenance of knowledge base has become main problem inartificial intelligence research. Knowledge domain become greater and need ofinteroperability with other application getting urgent. Knowledge base as the maincomponent in artificial intelligence architecture need to be modified to fullfil this change.Meanwhile the development of internet makes many standard launched to allow knowledgeexchange such as XML (extensible markup language), RDF (resources descriptionframework), DAML (DARPA agent markup language), OIL (ontology inference layer), OKBC(Open Knowledge-Base Connectivity). Frame based representation is one of knowledgerepresentation that can use for saving the knowledge and fact about some subject. This modelis supported by OKBC that can facilitate interoperability between knowledge base. Mainproblem that discussed in this paper is about the understanding and basic of knowledge basedevelopment with frame representation. To make more clear view a news paper case studytaken as sample how frame representation works as reusable component.Keywords: artificial intelligence, knowledge base, reusable knowledge base, framerepresentation system.